HCI International 2020 -- Late breaking papers : interaction, knowledge and social Media : 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings /: interaction, knowledge and social Media : 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings. (2020) - Unknown
No abstract available